Design of an Effective Accounting System in Financial Management at UD Pratama Jaya Furniture - Andreuw Kristian Pantow; Christony Maradesa; Wenny Anggeresia Ginting; Meike Negawati Kesek; Maykel Alexander Tampenawas (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
The design of an accounting system plays an important role in providing information for business decision-making. Most business entities in Indonesia are categorized as MSMEs, where accounting information continues to hold an essential role as the basis for decision-making to support future business development. An appropriate accounting system design can help MSMEs achieve their business objectives. UD Pratama Jaya Furniture is a micro business entity engaged in trade activities, focusing on the sale of various types of furniture. However, based on initial observations, the entity has not yet implemented a proper accounting system in its business operations. The research results include the design of an accounting system consisting of form or document designs, account codes, journals, ledgers, financial statements, as well as cash purchase and sales procedures. With a structured system in place, UD Pratama Jaya Furniture can record transactions systematically, reduce the risk of recording errors, present understandable financial information, and provide accurate data for decision-making.